Migração, escolarização e os alunos de educação de jovens e adultos - Moreira, Dayse Aline (2007)
This work had the purpose of drawing a profile of students who are attending nowadays Youth and Adults Education module, contrasting the characteristics of those ones who are in the first level to the ones who are in the final level of the basic school. This search was concluded in 2006 at a municipal school from São Paulo city, situated in a suburb area at Anhanguera São Paulo city, situated in a suburb area at Anhanguera Road border. This study arose from the hypothesis that there are permanencies and changes in the student profile when compared to the ones of students who attended the Adult Education in the past. The data for outlining the profile of the investigated persons were taken by a questionnaire which had forty questions about socioeconomic aspects and scholar course aspects. Twenty three students from first level have answered the questions and thirty one from the last level of Basic School, this way totalizing fifty four individuals. The data analysis was done with base on the Pierre Bourdieu ´s sociologic contributions. A great number of migrants composes the investigated individual s profile due to this, another purpose of this work is was to investigate if the experience of migration influenced the way on how the individuals live the scholar learning. Another point of analysis was to do a comparison between the sexes for investigating if men and women experience the scholar learning in different ways. The data tabulation showed that the individuals wish to continue their studies. It demonstrates how much they are investing on the growth of their cultural capital through the diploma materialized form of the cultural capital in the institutionalized state. The data were tabulated according to each level and demonstrate that the individuals from the final level (8 series) are more critic when referring the school, once only in this group of students appeared negative evaluations. The data were also tabulated considering the sex genre and showed that women had disadvantages referring the period the were out of the school. Another analysis axis was the comparison between migrants and non-migrants. This revealed the existence of likeness and differences between this two groups. The difference which called more attention was about alphabetization aspects with the individuals and with their parents too. In these aspects, the rates of migrants individuals are worse than the ones of non migrants